Analisis Kapasitas Faktor Produksi Berdasarkan Efisiensi dan Efektivitas Perusahaan dengan Metode Overall Equipment Efectiveness (OEE) (Studi pada CV. Litera Jannata Perkasa) - Lucky Prameswara Saputra; Lisa Sulistyawati (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine whether the elements of production factors including labor, raw materials and machinery affect the level of effectiveness and efficiency of accompany. This research uses CV object. Litera Jannata Perkasa which is engaded in manufacturing, the majority of which isin the form of book production. The sample was carried out by direct observation in the field and interviews with company parties. Thistest uses the overall Equipment Effectiveness (OEE) method which aims to measure how effective a company is with factors including Availability Ratio to measure the availability of raw materials and labor, Performance of production machines and Quality Ratio to measure the output of the company’s production process.